Chemisorption of toxic effluents from electroplating in residual gypsum from civil construction - Marinho, Jefferson Luiz Alves; Teixeira , Victor Feitosa; Teixeira, Raimundo Nonato Pereira (Seven Editora, 2024)
Some industrial sectors have an index of pollutants that are more degradable to the environment, for example, the electroplating industries. The treatment of its effluents is essential before it is released into water bodies. The purpose of this work is to test construction waste as possible adsorbents of toxic metal ions. Plaster was used as study material. Specimens were made with plaster moistened with contaminated solutions of Cu2+ and Pb2+. ions. The specimens were submitted to flexural strength tests and the results showed a small decrease in the strength of this type of material when compared to gypsum moistened with drinking water. Adsorption tests were also carried out using gypsum board residues. Kinetic studies showed an adsorption of the Pb2++ ion in a time of approximately 30 minutes. The adsorption isotherm tests showed an adsorptive capacity of approximately 88 mg/g New analyses should be carried out to verify the efficiency of the adsorption of other metal ions such as Cr, Ni and Cd from gypsum as adsorbent and other construction residues. DOI:https://doi.org/10.56238/sevened2023.001-015